Implikasi Hukum Putusan Pengadilan terhadap Pembatalan Perkawinan - Muchtar Anshary Hamid Labetubun; Sabri Fataruba (Batulis Civil Law Review, 2020)
Cancellation of a marriage begins after the Court decision has permanent legal force and is valid since the time the marriage takes place. The purpose of this study is to examine and analyze the legal implications of court decisions on cancellations made after marriage because it involves protecting the rights and obligations of the parties (husband and wife). The research method used is the type of normative research with a statutory approach, a conceptual approach and a case approach. The results showed that the cancellation of a marriage has permanent legal force, the separation is different from the husband and wife who separated due to divorce, but the obligation of iddah still applies to women whose marriage is canceled, while the provision of living has different provisions, namely, not getting a living from her ex-husband, because a marriage with a fasid contract that does not require a living. Cancellation of a marriage begins after a court decision has permanent legal force, and is effective from the time the marriage takes place.